2022
DOI: 10.1038/s41598-022-20404-3
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease: insights from a network medicine perspective

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease that currently lacks available effective therapy. Thus, identifying novel molecular biomarkers for diagnosis and treatment of AD is urgently demanded. In this study, we exploited tools and concepts of the emerging research area of Network Medicine to unveil a novel putative disease gene signature associated with AD. We proposed a new pipeline, which combines the strengths of two consolidated algorithms of the Network Medicine: DIseAse MOdule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Recent network-based approach studies have revealed that upregulation of SHIP2 (SH2 domain-containing Inositol 5-Phosphatase 2) transcripts encoded by INPPL1 (Inositol Polyphosphate Phosphatase Like 1) is significantly associated with cognitive decline and neuropathological lesions in human AD and aging brains [ 65 ] and that INPPL1 is one of the most significant AD-associated genes that can be potential diagnostic biomarkers and therapeutic targets for AD [ 24 ]. SHIP2 is one of the ten PI 5-phosphatases identified in the human genome [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent network-based approach studies have revealed that upregulation of SHIP2 (SH2 domain-containing Inositol 5-Phosphatase 2) transcripts encoded by INPPL1 (Inositol Polyphosphate Phosphatase Like 1) is significantly associated with cognitive decline and neuropathological lesions in human AD and aging brains [ 65 ] and that INPPL1 is one of the most significant AD-associated genes that can be potential diagnostic biomarkers and therapeutic targets for AD [ 24 ]. SHIP2 is one of the ten PI 5-phosphatases identified in the human genome [ 72 ].…”
Section: Introductionmentioning
confidence: 99%